Growth and yield performance of strawberry (Fragaria ananassa) under various doses of vermicompost and NPK fertilizers grown at rooftop of Charfasson area in the southern parts of Bangladesh - Rahman, Moomtahina; Alauddin, Md; Ali, AHM Zulfiquar (Dhaka University Journal of Biological Sciences, 2021)
A pot experiment was carried out on the rooftop of a building at Charfasson town Bhola to evaluate the growth and yield performance of strawberry (Fragaria ananassa) as influenced by different doses of vermicompost and inorganic fertilizers in the winter season of 2020-2021. Each pot was filled with ten kg soil and arranged in a completely randomized design having seven treatments with three replications. Treatments were T1: Control (-VC), T2: 5 t VC/ha, T3: 10 t VC/ha, T4: 15 t VC/ha, T5: 20 t VC/ha, T6: 25 t VC/ha, and T7: 50% RDF NPK (40 - 15-25 kg/ha). Different agronomic parameters were measured at the intervals of 30, 60, 90, and 120 days after sowing of seeds. All the treatments of vermicompost showed better responses in agronomic parameters than the control treatment. Among them, T5 treatment tends to show significantly (p<0.05) higher plant height (18.5 cm), number of the leaf (54/plant), root length (15.50 cm), first flowering (at 61 days), fruit length (5.75 cm), fruit diameter (13.75 cm), number of fruits (15/plant), the average weight of fruit (14.50 g), the fresh yield of fruits (13.59 t/ha), fresh weight of root (10.41 g/plant), fresh weight of reproductive structure (3.12 g/plant), weight of the dry reproductive structure (3.12 g/plant) and benefit-cost ratio (9.37). T6 treatment showed significantly (p<0.05) higher leaf area (49.00 cm2), fresh weight of petiole (4,61 g/plant), the weight of dry root (2.20 g/plant), weight of dry leaf (5.87 g/plant), weight of dry petiole (1.42 g/plant) and weight of dry biomass (12.48 g/plant). T2, T3 and T4 treatments showed significantly (p<0.05) higher growth than T7 treatment. The overall findings revealed that the application of vermicompost (20 t/ha) in the strawberry plant might be a suitable method in rooftop gardening to achieve its better agronomic and yield parameters in the southern parts of Bangladesh. Dhaka Univ. J. Biol. Sci. 30(2): 283-292, 2021 (July)